Formulation And Physical Stability Testing Of Emulgel Preparation Of Rainbow Leaf Extract (Eucalyptus Deglupta Blume) With Combination Of Carbopol 940 And Hpmc Gelling Agent Concentrations - Siti Saharah Abdullah; Taufiq Dalming; Ferawati Fajrin Abidin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Rainbow leaves are known to have antibacterial and anti-inflammatory activities, so they have the potential to be developed in the form of practical and comfortable topical emulgel preparations. This study aims to formulate and evaluate the physical stability of rainbow leaf extract emulgel preparations (Eucalyptus deglupta Blume) with variations in the combination of gelling agent concentrations Carbopol 940 and HPMC. Three emulgel formulas were made with different concentrations of Carbopol 940 and HPMC, then evaluated through organoleptic tests, homogeneity, pH, spreadability, adhesion, viscosity, and physical stability tests using the freeze-thaw method for 6 cycles. The evaluation results showed that all formulas met good physical parameters, with formula F1 (Carbopol 940 0.5% and HPMC 1.5%) showing the most optimal results in terms of viscosity, spreadability, and adhesion. Thus, the combination of Carbopol 940 and HPMC at optimal concentration can produce a physically stable rainbow leaf extract emulgel preparation that is suitable for topical application.